The Effectiveness Of Working While Studying For Military’s Cadets - et. al., Mohd Haizam Saudi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted to study the relationship between time management, self management, physiological needs and trainers on the effectiveness of military training while studying among cadet officers at National Defence University Malaysia (NDUM). The analysis used in this study is a quantitative analysis that uses descriptive data collected from questionnaires. A total of 250 respondents consisting of year two of Bachelor Cadet Officers were selected for this study. Data analysis method employed is Statistical Package for Social Science (SPSS) Version 22.0. Descriptive analysis was used to analyze the frequency, percentage and mean used while Pearson Correlation analysis and Linear Regression were used to test the independent and dependent variables formed. The findings of the study asserted a positive relationship to all independent variables namely time management, self management, physiological needs and trainers on the effectiveness of training while learning. In a nutshell, it was found that time-management needs are the most dominant factor on the effectiveness of military training while studying among Cadet Officers at National Defence University Malaysia (NDUM).